2019
DOI: 10.1186/s12879-019-4176-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the SpeeDx Carba (beta) multiplex real-time PCR assay for detection of NDM, KPC, OXA-48-like, IMP-4-like and VIM carbapenemase genes

Abstract: Background Carbapenemase-producing organisms (CPOs) have emerged as antibiotic-resistant bacteria of global concern. Here we assessed the performance of the Carba (beta) assay, a multiplex real-time PCR assay developed by SpeeDx for the detection of key carbapenemase-encoding genes: KPC, NDM, OXA-48-like, IMP-4-like, and VIM. Methods DNA extracts of 180 isolates were tested with the Carba (beta) assay, using previously validated in-house TaqMan probe assays for the rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…They con rmed the identi cation of NDM strains at dilution 103 and stated that the HRM method had limitations in the detection of different dilutions. Although identi cation of MBL and NDM strains has been performed in various studies in Sweden [28], USA [29], Australia [30], and Italy [31] in gram-negative Bacteria by HRM method, the novelty of the present study was the use of HRM method to identify P. aeruginosa PASGNDM699 strain. It was also found that the HRM method is highly potent in detecting PASGNDM699 strains that are resistant to colistin and carbapenem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They con rmed the identi cation of NDM strains at dilution 103 and stated that the HRM method had limitations in the detection of different dilutions. Although identi cation of MBL and NDM strains has been performed in various studies in Sweden [28], USA [29], Australia [30], and Italy [31] in gram-negative Bacteria by HRM method, the novelty of the present study was the use of HRM method to identify P. aeruginosa PASGNDM699 strain. It was also found that the HRM method is highly potent in detecting PASGNDM699 strains that are resistant to colistin and carbapenem.…”
Section: Discussionmentioning
confidence: 99%
“…DNA concentration was determined using a spectrophotometer Nanodrop-200 (Hangzhou Allsheng Instruments Co., Ltd, China). Primers sequence were initially set up as outlined in Ly et al [16], Bordin et al [6], Monteiro et al [17], Kosykowska et al [18], and Alkasaby et al [19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial carbapenem resistance was determined by measuring reduced susceptibility to ertapenem by disk diffusion; and DNA extracts of the isolates were PCR tested for the presence of carbapenemase determinants ( bla NDM , bla OXA-48 . bla KPC , bla VIM , and bla IMP types) as previously described [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…All K. pneumoniae samples ( n = 73) were further tested by a multiplex PCR method previously described (SpeeDx Pty Ltd., Australia) [ 27 ]. Briefly, samples were screened for carbapenemase genes bla KPC , bla NDM , bla OXA-48-like , bla IMP-4-like and bla VIM in a single multiplex reaction.…”
Section: Methodsmentioning
confidence: 99%